2007
DOI: 10.3201/eid1311.070367
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Eosinophilic Meningitis Cases Attributable toAngiostrongylus cantonensis,Hawaii

Abstract: During November 2004-January 2005, 5 cases of eosinophilic meningitis (EM) attributable to Angiostrongylus cantonensis infection were reported in Hawaii. To determine if this temporal clustering reflected an increased incidence, we ascertained EM and A. cantonensis cases by systematic review of statewide laboratory and medical records for January 2001-February 2005 and generalized the data to population estimates. We identified 83 EM cases; 24 (29%) were attributed to A. cantonensis infection, which was includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
58
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 32 publications
(79 reference statements)
1
58
1
1
Order By: Relevance
“…21,22 We previously reported a laboratory-and hospital-based investigation in Hawaii that included case data from January 2001 to February 2005. 23 In that study, we found a cluster of angiostrongyliasis cases that occurred on the island of Hawaii from November 2004 to February 2005. 23 We subsequently performed a retrospective analysis of cases from January 2003 to April 2005 (including the cluster cases) to ascertain clinical and epidemiologic characteristics.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…21,22 We previously reported a laboratory-and hospital-based investigation in Hawaii that included case data from January 2001 to February 2005. 23 In that study, we found a cluster of angiostrongyliasis cases that occurred on the island of Hawaii from November 2004 to February 2005. 23 We subsequently performed a retrospective analysis of cases from January 2003 to April 2005 (including the cluster cases) to ascertain clinical and epidemiologic characteristics.…”
Section: Introductionmentioning
confidence: 94%
“…23 In that study, we found a cluster of angiostrongyliasis cases that occurred on the island of Hawaii from November 2004 to February 2005. 23 We subsequently performed a retrospective analysis of cases from January 2003 to April 2005 (including the cluster cases) to ascertain clinical and epidemiologic characteristics. We report our findings here, with an emphasis on long-term sequelae and possible exposures for persons in Hawaii.…”
Section: Introductionmentioning
confidence: 94%
“…Finding the intact larvae during microscopic examination of the CSF is definitive, but this finding is rare, even in severe infections. [17][18][19] Detection of antibodies produced in response to the infection (immunodiagnosis) can be performed on serum or CSF using enzyme-linked immunosorbent assay (ELISA) or western blot (WB) techniques. However, these methods are not standardized and their diagnostic performance may vary depending on the purity of the native antigenic preparation used.…”
Section: Introductionmentioning
confidence: 99%
“…Signs of infection are related to migration of the larvae and associated multifocal eosinophilic inflammation. Symptoms can include headache, fever, malaise, nausea, neck stiffness, paraesthesias, urine and fecal retention, cranial nerve and ascending limb paralysis, seizures, coma, and death (Hochberg et al 2007;Diaz 2009;Ramirez-Avila et al 2009;Lunn et al 2012;Wang et al 2012). In humans, the disease is most often self-limiting with 2-8 weeks of severe headache and malaise (Hochberg et al 2001).…”
mentioning
confidence: 99%